Wordwall Supports Vocabulary Mastery in Vocational English for Specific Purposes (ESP) Learning: Wordwall Mendukung Penguasaan Kosakata dalam Pembelajaran Bahasa Inggris Kejuruan untuk Tujuan Tertentu (ESP) - Syarifah, Evy Lailatus; Fediyanto, Niko (Indonesian Journal of Education Methods Development, 2025)
General Background: Vocabulary acquisition is a crucial component of English language learning, particularly in English for Specific Purposes (ESP) at vocational high schools. Specific Background: Traditional teaching methods often fail to engage students effectively, leading to poor retention and limited practical application. Knowledge Gap: While various digital tools exist, research on the effectiveness of Wordwall in enhancing vocabulary retention in ESP contexts remains limited. Aims: This study investigates the impact of Wordwall on students' vocabulary acquisition and memory retention. Results: A quasi-experimental study using pre-tests and post-tests on two groups (experimental and control) revealed a significant improvement in vocabulary retention among students using Wordwall. The post-test scores of the experimental group (M=72.5) were significantly higher than the control group (M=58.5), supported by a Wilcoxon test (p<0.05). Novelty: Unlike conventional methods, Wordwall provides an interactive, gamified learning experience that enhances student motivation and engagement. Implications: These findings suggest that integrating Wordwall into ESP instruction can effectively support vocabulary development, promoting better language proficiency and practical communication skills in vocational education. Future research should explore its application across diverse educational settings. Highlights: Interactive Learning Enhances Retention – Wordwall's gamified approach significantly improves vocabulary retention compared to traditional methods. Significant Performance Improvement – Students using Wordwall scored notably higher (M=72.5) than the control group (M=58.5), proving its effectiveness. Practical Implications for ESP – Integrating Wordwall into vocational education fosters engagement, making language learning more relevant and effective. Keywords: Memorial, Wordwall, Vocabulary Acquisition, English for Specific Purposes, Digital Learning